2010
DOI: 10.21002/jaki.2010.07
|View full text |Cite
|
Sign up to set email alerts
|

Stock Split Dan Likuiditas Saham Di Bei: Pengujian Menggunakan Hipotesis Likuiditas

Abstract: This study aims to re-examine the effectiveness of liquidity hypothesis in stock split. Liquidity hypothesis in stock split is defined as the returning stock price to the optimal trading level. Based on Ekaputra and Putri (2006) Ekaputra and Putri (2006) and in line with Kim et al. (2007)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
1
0
1
Order By: Relevance
“…It caused a decrease in stock liquidity individually or as a portfolio. Then, Setyawan (2010) examined all go public companies listed on the stock exchange. It was shown that stock return declined after the stock split.…”
Section: Introductionmentioning
confidence: 99%
“…It caused a decrease in stock liquidity individually or as a portfolio. Then, Setyawan (2010) examined all go public companies listed on the stock exchange. It was shown that stock return declined after the stock split.…”
Section: Introductionmentioning
confidence: 99%
“…Saham dibagi sebab ada limit harga maksimum yang menyebabkan nilai saham diperdagangkan di pasar menurun dengan harapan dapat meningkatkan minat investor, sehingga mengakibatkan peningkatan pada likuiditas perdagangan (Indarti dan Purba, 2011). Hal ini disebabkan oleh perusahaan yang biasanya menggunakan metode relative atau bid-ask spread untuk ukuran likuiditas, di mana penawaran dan permintaan dalam buku limit order termasuk unsur harga saham yang akan bertemu pada titik keseimbangan tertentu dan menghasilkan suatu harga pasar (Setyawan, 2010).…”
Section: Optimal Trading Rangeunclassified